Isolation and characterization of human mammary stem cells - Clarke, R. B. (Cell Prolif, 2005)
Abstract.  Since stem cells are present throughout the lifetime of an organism, it is thought that they may accumulate mutations, eventually leading to cancer. In the breast, tumours are predominantly oestrogen and progesterone receptor‐positive (ERα/PR+). We therefore studied the biology of ERα/PR‐positive cells and their relationship to stem cells in normal human mammary epithelium. We demonstrated that ERα/PR‐positive cells co‐express the putative stem cell markers p21(CIP1/WAF1), cytokeratin (CK) 19 and Musashi‐1 when examined using dual label immunofluorescence on tissue sections. Next, we isolated a Hoechst dye‐effluxing ‘side population’ (SP) from the epithelium using flow cytometry and demonstrated them to be undifferentiated cells by lack of expression of myoepithelial and luminal cell‐specific antigens such as CALLA and MUC1. Epithelial SP cells were shown to be enriched for the putative stem cell markers p21(CIP1/WAF1), Musashi‐1 and ERα/PR‐positive cells. Lastly, SP cells, compared to non‐SP, were highly enriched for the capacity to produce colonies containing multiple lineages in 3D basement membrane (Matrigel) culture. We conclude that breast stem cells include two populations: a primitive ERα/PR‐negative stem cell necessary for development and a shorter term ERα/PR‐positive stem cell necessary for adult tissue homeostasis during menstrual cycling. We speculate these two basic stem cell types may therefore be the cells of origin for ERα‐positive and ‐negative breast tumours.